Hyperlipidemia Diet Reduces Superoxide Dismutase Inhibition Rate in the Brain Organ of Rattus norvegicus - Muhammad Luthfi Adnan; Miranti Dewi Pramaningtyas; Dini Islamiana; Hilmi Ardian Sudarto (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Quail (Coturnix coturnix japonica L.) egg yolk is one of the high-fat foods which can trigger hyperlipidemia. The condition of hyperlipidemia can have an oxidative stress effect on the brain. Superoxide dismutase (SOD) is a natural antioxidant that acts as a defense mechanism against oxidative stress. The inhibition rate of SOD decreases when oxidative stress occurs. This study aims to determine the effect of quail egg yolk on the SOD inhibition rate of brain organs on a rat. This study used male Wistar rats aged 2-3 months with 200-300 grams of weight. The rats were divided into two groups. Each group was fed with ad libitum for two weeks. The A groups as control continued ad libitum consumption, and the B group was given additional quail egg yolk 5 ml / 200 g BW for 2 weeks. At the end of the study, the rats were terminated. The brain organs were examined for SOD inhibition rate with spectrophotometry. The mean SOD inhibition rate in the A and B groups was 74.14% ± 6.16 and 24.14% ± 5.65, respectively. The independent t-test showed significant differences in SOD inhibition rate between groups (p 0.001). Furthermore, quail egg yolk significantly reduced the SOD inhibition rate in the brain organ of the rat.